Perancangan Sistem Penjualan Online Berbasis Web Pada Toko Longgtime.Id Menggunakan Metode Waterfall - Gilang Nur Dwiasyah; Muhammad Alfito Risky Pratama; Irfan Maulana; Saprudin (CV. Shofanah Media Berkah, 2023)
E-commerce is a way for people to meet their needs in the midst of their daily activities. In Indonesia, there are many market places that provide e-commerce services. With so many e-commerce providers, there are also many problems that arise in it. This study aims to determine the implementation of buying and selling transactions on website-based applications, to find out the factors that encourage people to make buying and selling transactions online, to find out the efficiency of consumers who make buying and selling transactions online through online applications. The research method used is the waterfall method which is linear sequential in that the process of working on a system is carried out sequentially and systematically. The primary data collection technique is by interviewing and secondary data by reading, reviewing, and analyzing primary legal materials, secondary legal materials, and tertiary legal materials. The analysis technique used is qualitative analysis, which is interpreted logically and systematically and then conclusions are drawn. Based on the results of the study that carry out website-based transactions by logging in, searching for goods, submitting an offer or buying, entering an email, entering the delivery address, delivery service, and payment method, then making a payment. Factors that encourage people to do e-commerce because it is more efficient, cheaper, and more practical.